PENGEMBANGAN MEDIA KARTU TOPIK TRIGONOMETRI KELAS X SMAN 4 MALANG - Sunaifah, Ivatus (Jurnal Likhitaprajna, 2019)
Mathematics is a universal science that underlies the development of modern technology. Mathematics learning is done through communication between teachers and students with tools both in the form of audio-visual and print. Media is a tool for the learning process to clarify the meaning of the message delivered, so that it can achieve the learning objectives better and more perfectly. The use of media is not judged by the sophistication of the media but more important is the function and role in helping the learning process. This development research aims to produce media for the topic of trigonometric equations. This media is designed to be applied in cooperative learning and aims to improve students' problem solving abilities. Media development was carried out using the 4D model (Define, Design, Develop, Disseminate). To get media that is valid, practical and effective in accordance with the criteria set by the author, the researcher compiles the RPP and research instruments supporting the implementation of the media. The validation results indicate that the media and supporting instruments have met the validity criteria. The results of trials in the field indicate that the media has met the criteria of practicality and effectiveness.Keywords: development, card media, trigonometry